Tianma Gouteng granules decreases the susceptibility of Parkinson's disease by inhibiting ALOX15-mediated lipid peroxidation. (28th June 2020) - Jiang, Ying-Nan; Guo, Yong-Zhi; Lu, Dan-Hua; Pan, Ming-Hai; Liu, Hai-Zhi; Jiao, Gen-Long; Bi, Wei; Kurihara, Hiroshi; Li, Yi-Fang; Duan, Wen-Jun; He, Rong-Rong; Yao, Xin-Sheng
Abstract: Ethnopharmacological relevance: Tianma Gouteng granules (TG), a clinical prescription of traditional Chinese medicine, has been clinically applied to treat Parkinson's disease (PD) in combination with Madopar, as included in the Chinese Pharmacopoeia (2015). TG has the potential to decrease the susceptibility of PD pharmacologically, however the mechanisms need detailed demonstration. Aim of the study: To evaluate the pharmacological activities, as well as the possible mechanism of TG in diverse models of PD. Materials and methods: 6-OHDA-treated rats, MPTP-treated mice, and α-synuclein A53T overexpressed mice, were utilized as PD animal models. Rotarod, locomotor activity, inclined plane and traction tests were used for behavioral assessment. Immunohistochemistry was used for tyrosine hydrolase determination. Western blot were conducted for detection of 4-HNE and 15-lipoxygenase-1 (ALOX15). The interactions of ALOX15 with the components in TG were predicted by molecular docking approach. Results: Lipid peroxidation was involved in dopaminergic neuron damage in 6-OHDA-induced rat models. In MPTP-treated mice, the inhibition of lipid peroxidation improved behavioral and pathological symptoms of PD. The lipid peroxidation-related protein, ALOX15 was found to be the key factor in PD process in diverse PD models including 6-OHDA-treated rats, MPTP-treated mice, and α-synuclein A53T overexpressed mice. TG treatment significantly relieved behavioral and pathological symptoms of MPTP-induced PD mouse models with a potential mechanism of alleviating ALOX15-induced lipid peroxidation. Moreover, the results of molecular docking analysis show that compounds in TG might have interactions with ALOX15. Conclusions: TG effectively improved the behavioral and dopaminergic neuron damage in diverse PD models. The mechanism of this action may be related to the direct inhibition of ALOX15 and the relief of lipid peroxidation. Graphical abstract: Image 1